Solares ludovicenses: entre a etimologia e a tipologia, a criação de um patrimônio - Cláudia Nunes de Lima e Andrade (2020)
The present research seeks to unravel the emergence and production conditions of eleven buildings in Sao Luis, Maranhão, recognized as “solares” by heritage protection agencies and their interrelationship with the local architectural culture. These buildings are specimens of the exponent residential architecture produced during the “Golden Age” in Maranhão. Besides the exceptional construction techniques applied, bonds with historic facts and characters from Maranhão, which vested these buildings with monument statuses, their dimensions allow numerous uses. However, the new uses which vest them with cultural resignification put them at risk of losing their integrity and authenticity. These risks are increased by the lack of specialized literature embracing the specificities of São Luis manor houses typologies. Therefore, the present research intends to narrow the knowledge gap on São Luis’s dwellings by pointing up the typological characteristics of solares, distinguishing their architectonic material composition from other 19th-century residential building typologies, unveiling temporally the role of “solar” denomination in relation to respective construction and their social, cultural and political representations, verifying the adequacy of the nomenclature for the buildings called this way. By filling in this gap, it will provide a robust theoretical framework on solares in Sao Luis, contributing to their interpretation and integrity preservation in future interventions.